Evidence from Phylogenomics and Morphology Provide Insights into the Phylogeny, Plastome Evolution, and Taxonomy of Kitagawia - Jia-Qing Lei; Chang-Kun Liu; Jing Cai; Megan Price; Song-Dong Zhou; Xing-Jin He (Plants, 2022)
Kitagawia Pimenov is one of the segregate genera of Peucedanum sensu lato within the Apiaceae. The phylogenetic position and morphological delimitation of Kitagawia have been controversial. In this study, we used plastid genome (plastome) and nuclear ribosomal DNA (nrDNA) sequences to reconstruct the phylogeny of Kitagawia, along with comparative plastome and morphological analyses between Kitagawia and related taxa. The phylogenetic results identified that all examined Kitagawia species were divided into Subclade I and Subclade II within the tribe Selineae, and they were all distant from the representative members of Peucedanum sensu stricto. The plastomes of Kitagawia and related taxa showed visible differences in the LSC/IRa junction (JLA) and several hypervariable regions, which separated Subclade I and Subclade II from other taxa. Fruit anatomical and micromorphological characteristics, as well as general morphological characteristics, distinguished the four Kitagawia species within Subclade I from Subclade II and other related genera. This study supported the separation of Kitagawia from Peucedanum sensu lato, confirmed that Kitagawia belongs to Selineae, and two species (K. praeruptora and K. formosana) within Subclade II should be placed in a new genus. We believe that the “core” Kitagawia should be limited to Subclade I, and this genus can be distinguished by the association of a series of morphological characteristics. Overall, our study provides new insights into the phylogeny, plastome evolution, and taxonomy of Kitagawia.